LASER LEVELING OF SOIL IN THE PRE-SEASON PERIOD FOR LEVELING SOIL RELIEF IN «THE TST AGRO CLUSTER «NIZHNECHIRCHIK» DISTRICT TASHKENT REGION» (World Bulletin of Management and Law, 2023)
This article presents methods for leveling the soil before the pre-sowing period using laser leveling in the Nizhnechirchik district of the Tashkent region.